ANALISIS MOTIVASI KERJA KARYAWAN PADA PT. RIAU KARSA PELITA PEKANBARU - Elvi "; Syofia Achnes; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research aims to find out how employee motivation at PT. Riau Karsa Pelita and to find out what factors that affect employee motivation at PT. Riau Karsa Pelita.This research uses descriptive quantitative methods to find out how employee motivation at PT. Pelita Pekanbaru Riau Karsa. As for the respondents in use are all employees of PT Riau Karsa Pelita is drawn using census methods. While the data collection technique in this study using observation, interviews, and questionnaires. By using a Likert scale as a gauge to determine the length of the short interval that can be used to generate quantitative data.Based on the research results, PT Riau Karsa Pelita have noticed employee motivation viewed by using the theory of Maslow's hierarchy of needs are: Physiological Needs, Safety Needs, socializing needs, esteem needs and self-actualization needs. According to respondents, the motivation of the employees working at PT Riau Karsa Pelita included in the high category.Keywords : motivation, human and needs